ANALISIS PRODUKSI ALAT MUAT DAN ALAT ANGKUT PADA PENGUPASAN OVERBURDEN PT. WIJAYA INTI NUSANTARA KABUPATEN KONAWE SELATAN PROVINSI SULAWESI TENGGARA - Ariel; Hendra Sani; Ruth Bunga R (Journal Teknik Dan Teknologi, 2025)
Loading and transporting overburden is one of the activities carried out in nickel mining by moving overburden from the mining front to the disposal site. Research Objectives: 1) Determine the efficiency of loading and transporting equipment in loading and transporting overburden. 2) The production capacity of loading and transporting equipment used in loading and transporting overburden. 3) The compatibility factor between loading and transporting equipment used in loading and transporting overburden. The methods used in this study were interviews and observation. The interview method was conducted with people in the company area regarding data to be collected at the company itself. Then, the observation method involved directly observing the data to be collected at the company. The results achieved in this study are the work efficiency value for loading equipment is 83% and for transport equipment is 83%, the production of 1 unit of loading equipment is 37,788.16 Bcm/month and 4 units of transport equipment is 37,333.6 Bcm/month so that it has met the target, the work harmony factor of loading equipment and transport equipment is 0.98 so that MF<1, which means that the transport equipment is working fully and the loading equipment still has waiting time. It is necessary to add transport equipment so that the loading equipment does not have waiting time.